Pengembangan LKPD Dengan Model Kooperatif Think Talk Write (TTW) Berbasis Animasi Untuk Meningkatkan Keterampilan Menulis Narasi Pada Murid Kelas III Di SDN 10 Tandikat Agam - Nur Hafizah; Vini Wela Septiana (Suluah: Journal of Insight, 2026)
Suboptimal learning processes and unengaging instructional media often become problems in schools, resulting in students’ low narrative writing skills. In this context, appropriate instructional tools are needed to achieve learning objectives, one of which is the Student Worksheet (LKPD). LKPD is an educational resource that presents materials and task instructions systematically to support students’ learning activities. Therefore, an LKPD based on the cooperative learning model Think Talk Write (TTW) assisted by animation was developed and categorized as valid, practical, and effective to improve students’ narrative writing skills.           This study employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. Product validity was assessed by expert validators, practicality was evaluated by teachers through questionnaires, and effectiveness was measured through students’ responses and test results.          The results showed that the TTW-based LKPD met the three evaluation criteria. First, the product validity score reached 87% (very valid). Second, the practicality score was 94% (very practical). Third, the effectiveness score was 86% (very effective). Thus, the LKPD is considered feasible and effective for use in learning activities in Grade III at SDN 10 Tandikat.